PENGEMBANGAN MODUL CERITA BERGAMBAR BERBASIS E-LEARNING MATERI AKTIVITAS EKONOMI PADA MATA PELAJARA IPS - Nopiani; Nana Hendracipta; A. Syachruroji (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to know the development and worthiness of the pictorial story modules based on e-learning for the materials of economic activities on the social science subject, and to know learners' responses to the pictorial story modules based on e-learning for the materials of economic activities on the social science subject. The method used in this study was the research and development (RND) from Borg & Gall. This development used only 6 steps out of 10 steps, because of the time limit and the cost of researchers. The product assessment for the module's worthiness test was conducted by three experts: media experts, linguists, and materials experts, with the test subjects of scale limited to 20 students at Class IV-B of SD Negeri 13. The results of the feasibility of the module were 88%, meaning that the percentage value was categorized as